Integrasi Teknologi dalam Pengelolaan Kurikulum Pondok Pesantren Modern: Tren, Tantangan, dan Peluang - Syaharuddin Syaharuddin; Yudin Citriadin; Alfira Mulya Astuti (Universitas Muhammadiyah Mataram, 2026)
Abstract: Technology integration in curriculum management is a crucial aspect of educational transformation in modern Islamic boarding schools. The use of technology not only supports administrative digitization but also contributes to data-driven educational planning, implementation, evaluation, and decision-making. This study aims to identify trends in technology integration in curriculum management in modern Islamic boarding schools, analyze implementation challenges, and explore opportunities to improve the quality of Islamic boarding school education in the digital era. The study employed a qualitative approach using the Systematic Literature Review (SLR) method. Data were obtained from the Scopus, DOAJ, Dimensions, and Google Scholar databases, with publications spanning 2017–2025. The study results indicate that technology integration is evolving from a focus on infrastructure and digital literacy to digital transformation encompassing academic information systems, educational governance, data-driven curriculum evaluation, and the implementation of the Independent Curriculum. Key challenges include limited infrastructure, human resource digital competency, and organizational readiness to manage change. On the other hand, technology opens up opportunities for developing a more adaptive, innovative, and student-oriented curriculum. These findings indicate that technology integration plays a strategic role in supporting the modernization and continuous improvement of the quality of education in modern Islamic boarding schools.Abstrak: Integrasi teknologi dalam pengelolaan kurikulum menjadi salah satu aspek penting dalam transformasi pendidikan di pondok pesantren modern. Pemanfaatan teknologi tidak hanya mendukung digitalisasi administrasi, tetapi juga berkontribusi terhadap perencanaan, implementasi, evaluasi, dan pengambilan keputusan pendidikan berbasis data. Penelitian ini bertujuan untuk mengidentifikasi tren integrasi teknologi dalam pengelolaan kurikulum pondok pesantren modern, menganalisis tantangan implementasinya, serta mengeksplorasi peluang yang dapat dimanfaatkan untuk meningkatkan kualitas pendidikan pesantren di era digital. Penelitian menggunakan pendekatan kualitatif dengan metode Systematic Literature Review (SLR). Data diperoleh dari database Scopus, DOAJ, Dimensions, dan Google Scholar dengan rentang publikasi tahun 2017–2025. Hasil kajian menunjukkan bahwa integrasi teknologi berkembang dari fokus pada infrastruktur dan literasi digital menuju transformasi digital yang mencakup sistem informasi akademik, tata kelola pendidikan, evaluasi kurikulum berbasis data, dan implementasi Kurikulum Merdeka. Tantangan utama meliputi keterbatasan infrastruktur, kompetensi digital sumber daya manusia, serta kesiapan organisasi dalam mengelola perubahan. Di sisi lain, teknologi membuka peluang pengembangan kurikulum yang lebih adaptif, inovatif, dan berorientasi pada kebutuhan peserta didik. Temuan ini menunjukkan bahwa integrasi teknologi berperan strategis dalam mendukung modernisasi dan peningkatan mutu pendidikan pondok pesantren modern secara berkelanjutan.